2007
DOI: 10.1016/j.febslet.2007.09.022
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of proliferating cell nuclear antigen (PCNA) isoforms in normal and cancer cells: There is no cancer‐associated form of PCNA

Abstract: In order to clarify the status of PCNA in normal and transformed cells, we performed analysis of this protein by 2D-PAGE, Western blot and mass spectrometry. All the cell lines examined contained the major PCNA form (pI 4.57/30 kDa), that is not post-translationally modified. In addition to the major form, two minor isoforms (pI 4.52/30 kDa and pI 4.62/30 kDa) were also detected in all the cell lines examined. However, the level of PCNA in cancer cells is 5-6 folds higher than those in primary and most of the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
45
0
4

Year Published

2010
2010
2020
2020

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 50 publications
(52 citation statements)
references
References 18 publications
3
45
0
4
Order By: Relevance
“…As expected from our previous work [18], the level of PCNA protein was much higher in MDA-MB468 than HMEC (compared Fig. 1A vs C).…”
Section: Identification Of Pcna-binding Proteins In Normal and Cancersupporting
confidence: 89%
See 1 more Smart Citation
“…As expected from our previous work [18], the level of PCNA protein was much higher in MDA-MB468 than HMEC (compared Fig. 1A vs C).…”
Section: Identification Of Pcna-binding Proteins In Normal and Cancersupporting
confidence: 89%
“…A PCNA ring may bind to different protein partners at different time and space to carry out specific tasks [3,5,16,17]. We previously found that the level of PCNA is substantially elevated in cancer cells, which is only notable difference between cancer and normal cells with respect to PCNA protein [18]. Since PCNA-protein interactions may be affected by elevated protein concentration at a given time and space, our finding raises the possibility that PCNA in cancer cells may interact with certain proteins that do not normally interact with PCNA in normal cells.…”
Section: Introductionmentioning
confidence: 99%
“…In-gel trypsin digestion and generation of peptide spectra by matrix-assisted laser desorption/ionization were performed as described previously, with some modifications (Naryzhny and Lee, 2007). The produced peptides were collected directly from the gel plug digest, mixed (1:1) with a-cyano-4-hydroxycinnamic acid matrix solution (Fluka, Buchs, Switzerland), 10 mg/ml, in 50% acetonitrile, 20% ethanol, 0.01% trifluoroacetic acid, applied to the target plate, crystallized and analyzed by matrix-assisted laser desorption/ionization on a Micro MX instrument (Waters Inc., Milford, MA, USA).…”
Section: Transformation In Vitro Assaymentioning
confidence: 99%
“…Все процедуры проводили, следуя протоколу, описанному ранее [15]. После разделения с помощью 2DE и окрашивания с использованием Кумасси R350 кусочки геля диаметром 1,5 мм, соответствующие белковым пятнам, вырезали, используя наконечники для микропипеток, и частично обесцвечивали 15-минутной инкубацией в 500 мкл 50%-ного ацетонитрила (ACN), содержащего 25 мМ бикарбонат аммония.…”
Section: иммуноблотинг (вестерн-блот)unclassified
“…Образцы готовили, по описанной ранее методике [15,16]. Клетки (~10 7 ), содержащие до 2 мг белка, лизировали в 100 мкл буфера (7 М мочевина, 2 М тиомочевина, 4% CHAPS, 1% дитиотреитол (ДTT), 2% амфолиты, pH 3-10, смесь протеазных ингибиторов).…”
unclassified